Dynamic simulation of an original Joule cycle liquid pistons hot air Ericsson engine. (1st January 2020) - Ngangué, Max Ndamé; Stouffs, Pascal
Abstract: An Ericsson engine is an external heat supply engine working according to a Joule thermodynamic cycle. It is based on reciprocating piston-cylinder machines. Such engines are especially interesting for low power solar energy conversion, micro-CHP from conventional fossil fuels or from biomass and waste heat recovery. An innovative configuration has been designed where the mechanical pistons are replaced by liquid pistons. The engine is composed of two U-shape tubes partially filled with water, one for the compression spaces and one another for the expansion spaces. A thermodynamic model of the engine is developed. The model takes into account the dynamics of the liquid columns. It is shown that the engine indicated efficiency decreases when the rotation speed increases. The sign of the instantaneous torque on the flywheel changes four times per cycle, calling for a heavy flywheel. When the rotation speed increases above the natural frequency of oscillation of the liquid columns, the influence of the liquid pistons inertia is growing. Its impact is globally opposite to the one of the pressure in the cylinders. So, the effect of the inertia of the liquid columns is to reduce the amplitude of the torque variations. Highlights: An innovative configuration of an Ericsson engine is presented. It is easy to build and suited for small scale renewable thermal energy conversion. A model is developed. The mean torque decreases as the rotational speed increases. The effect of the inertia of the liquid columns is to reduce the amplitude of the torque variations.